p62 Overexpression Promotes Bone Metastasis of Lung Adenocarcinoma out of LC3-Dependent Autophagy - Li, Dongqi; He, Chuanchun; Ye, Fan; Ye, En; He, Hao; Chen, Gong; Zhang, Jing (Frontiers in Oncology, 2021)
p62 protein has been implicated in bone metastasis and is a multifunctional adaptor protein usually correlated with autophagy. Herein, we investigated p62 expression and its prognostic significance in bone metastasis of lung adenocarcinoma, and analyzed whether the mechanism involved depends on autophagy. mRNA and protein expression of p62, LC3B and Beclin 1 were detected by reverse transcription-quantitative PCR and western blotting, respectively, in fresh bone metastasis tissues (n=6 cases) and normal cancellous bone tissues (n=3 cases). The association between p62 and LC3B expression and patient prognosis was subsequently analyzed in 62 paraffin-embedded bone metastasis specimens by immunohistochemistry assay. Small interfering RNA (siRNA) was employed to downregulate p62 expression in SPC-A-1 and A549 cells. Cell proliferation and migration ability were tested by CCK8, CCF and Transwell assays respectively. Autophagy was induced by Rapamycin or inhibited by Atg 7 knockout/Chloroquine in A549 cells and p62 and LC3Ⅱ/Ⅰ expression were analysed. After subcutaneous inoculation or intracardial injection of A549 cells into nude mice, the effect of p62 downregulation in vivo was analysed by histopathological examination. The results showed that p62, LC3B and Beclin 1 mRNA and protein were all overexpressed in bone metastasis tissues (all P<0.01). Patient samples with high p62 expression levels were significantly associated with more bone lesions (>3), shorter overall survival rates and shorter progression free survival rates compared with patients having lower p62 expression (P=0.014, P=0.003, P=0.048, respectively). Cox regression analysis identified p62 expression as an independent prognostic indicator of overall survival of patients with bone metastasis (P=0.007). In vitro p62 downregulation inhibited SPC-A-1 and A549 cells migration but had no effect on cell proliferation. After autophagy induction or inhibition, p62 expression involved in autophagy flux and changed inconsistently according to the switch of LC3I to LC3Ⅱ in different autophagy conditions. In vivo p62 downregulation had no effect on growth of subcutaneous tumor. Lung or bone metastasis lesion was not found in all mice model. These findings suggested that p62 overexpression promotes tumor cell invasion out of LC3-dependent autophagy, which could be used a potential prognostic biomarker and therapeutic target for bone metastasis of lung adenocarcinoma.